Hubungan Antara Self-Efficacy dan Critical Thinking Mahasiswa dalam Menggunakan AI pada Mata Kuliah Teori Bilangan - Raharjo, Sigit; Haswati, Desty; Aisyah, Siti Nur; Marlina; Khairunnisa, Mutia (Jurnal PEKA (Pendidikan Matematika), 2025)
This reserch aims to analyze the relationship between students’s self-efficacy and critical thingking in using artificial intelligence (AI) in Number Theory course. The method used in quantitative survey with a correlation approach. The research sample consisted of 30 students in the 5th semester of the Mathematics Education Study Program, Muhammadiyah University, Tangerang. Data was collected through questionnaires and critical thingking tests. The research result show that the majority of students are in the medium category in terms of self-efficacy, critical thingking skills, and use of AI. The correlation test shows that there is no significant relationship between self-efficacy and critical thingking on the use of AI. It is hoped that the results of this research can be a reference in developing learning strategies that utilize AI effectively by considering other factors.